Equivalent constant-amplitude fatigue load method based on the energy equivalence principle. Issue 13 (October 2019) - Gao, Ruofan; Li, Jie
An equivalent constant-amplitude cyclic loading method for random vehicle load is proposed based on the concept of energy equivalence. The filtered compound Poisson process is adopted to describe random vehicle load, through which the vehicle load spectrum is gained. The total dissipated energy due to fatigue loads subjected to concrete structures is deduced by introducing a multi-scale model, in which the energy dissipation induced by the nano-cracks level is presented, and the energy transition from nano to macro scales is derived. By assuming that the total energy dissipation under random loading equals that under equivalent constant-amplitude loading, the equivalent load ratio and amplitude as well as the number of equivalent cycles for random vehicle load are obtained. To validate the effectiveness of the proposed method, a set of numerical simulations is presented. The fatigue damage accumulations for concrete structures under both the random load and the equivalent loads converted by the proposed method and the classic root mean square method are calculated. By comparing with the root mean square method, the accuracy and advantage of the proposed equivalent load model are verified.